Cloud computing and security issues in the cloud (Trinity Journal of Management, IT & Media (TJMITM), 2018)
Cloud computing has formed the conceptual and  infrastructural basis for tomorrow's computing. The global  computing infrastructure is rapidly moving towards cloud  based architecture. While it is important to take advantages  of cloud based computing by means of deploying it in  diversified sectors, the security aspects in a cloud based  computing environment remains at the core of interest.  Cloud based services and service providers are being  evolved which has resulted in a new business trend based  on cloud technology. With the introduction of numerous  cloud based services and geographically dispersed cloud  service providers, sensitive information of different entities  are normally stored in remote servers and locations with  the possibilities of being exposed to unwanted parties in  situations where the cloud servers storing those  information are compromised. If security is not robust and  consistent, the flexibility and advantages that cloud  computing has to offer will have little credibility. This paper  presents a review on the cloud computing concepts as well  as security issues inherent within the context of cloud  computing and cloud infrastructure.
Keywords: Cloud computing; cloud service; cloud security; computer network; distributed computing; security